Boosting the Optimization of Lithium Metal Batteries by Molecular Dynamics Simulations: A Perspective. Issue 41 (27th September 2020) - Sun, Yawen; Yang, Tingzhou; Ji, Haoqing; Zhou, Jinqiu; Wang, Zhenkang; Qian, Tao; Yan, Chenglin
Abstract: The Li metal battery is attracting more and more attention in the field of electric vehicles because of its high theoretical capacity and low electrochemical potential. But its inherent disadvantages including uncontrolled lithium dendrites, high chemical activity, and large volume changes hold back the large‐scale application of stable Li metal anodes. Recently, various computational studies have been used to facilitate the rationalization of experimental observed phenomenon. In this review, the progress of molecular dynamics simulations in Li metal batteries is highlighted. Molecular dynamics simulations can predict how selected atoms in different systems of Li metal battery will move over time based on a general model of the physics governing interatomic interactions. The analysis of the transport structure of Li ions, the electrochemical process at electronic, atomic, or molecular level, the Li + transport mechanism, and the Li deposition behavior are described in detail. Some suggestions are also made about the further potential of molecular dynamics simulations do in Li metal batteries are also made. Abstract : Li metal batteries (LMB) have regained broad interest in the energy storage system field, thanks in part to the use of molecular dynamics (MD) simulation in the rational design of LMBs. The progress of MD simulations in LMBs with respect to the electrolyte, solid electrolyte interphase, and Li deposition behavior are summarized.